Dynamic contrast‐enhanced MRI of the prostate with high spatiotemporal resolution using compressed sensing, parallel imaging, and continuous golden‐angle radial sampling: Preliminary experience. Issue 5 (16th May 2014) - Rosenkrantz, Andrew B.; Geppert, Christian; Grimm, Robert; Block, Tobias K.; Glielmi, Christian; Feng, Li; Otazo, Ricardo; Ream, Justin M.; Romolo, Melanie Moccaldi; Taneja, Samir S.; Sodickson, Daniel K.; Chandarana, Hersh
<x xml:space="preserve">Abstract</x> Purpose To demonstrate dynamic contrast‐enhanced (DCE) magnetic resonance imaging (MRI) of the prostate with both high spatial and temporal resolution via a combination of golden‐angle radial k‐space sampling, compressed sensing, and parallel‐imaging reconstruction (GRASP), and to compare image quality and lesion depiction between GRASP and conventional DCE in prostate cancer patients. Materials and Methods Twenty prostate cancer patients underwent two 3T prostate MRI examinations on separate dates, one using standard DCE (spatial resolution 3.0 × 1.9 × 1.9 mm, temporal resolution 5.5 sec) and the other using GRASP (spatial resolution 3.0 × 1.1 × 1.1 mm, temporal resolution 2.3 sec). Two radiologists assessed measures of image quality and dominant lesion size. The experienced reader recorded differences in contrast arrival times between the dominant lesion and benign prostate. Results Compared with standard DCE, GRASP demonstrated significantly better clarity of the capsule, peripheral/transition zone boundary, urethra, and periprostatic vessels; image sharpness; and lesion conspicuity for both readers (P < 0.001–0.020). GRASP showed improved interreader correlation for lesion size (GRASP: r = 0.691–0.824, standard: r = 0.495–0.542). In 8/20 cases, only GRASP showed earlier contrast arrival in tumor than benign; in no case did only standard DCE show earlier contrast arrival in tumor. Conclusion High spatiotemporal resolution prostate DCE is possible with GRASP, which has the potential to improve image quality and lesion depiction as compared with standard DCE. J. Magn. Reson. Imaging 2015;41:1365–1373. © 2014 Wiley Periodicals, Inc.